Housing conditions, knowledge and perceived health effects of indoor air pollution in tribal women of rural Maharashtra - Shah, Anuradha Kunal; Yetalkar, Ashwini D.; Kaware, Alka C. (International Journal of Research in Medical Sciences, 2020)
Background: Dependence on using biomass fuels for cooking and heating leads to Indoor Air Pollution (IAP) which can lead to adverse health outcomes. Aim of this study was to observe the housing and kitchen conditions in households of tribal areas, assess the knowledge of women regarding the IAP and perceived health effects due to it. Methods: Cross-sectional community- based study conducted in 100 women above the age of 18 years in a tribal village. A semi-structured questionnaire was used and spot observations were made. Chi-Square was used to calculate the association between type of stove, housing conditions and health effects of IAP. Logistic regression was used to identify determinants of the health effects of IAP. Results: The mean age of women was 29 years; all houses had a separate kitchen; 34% used mud stove with wood. Easy availability and economic reasons were cited for using wood. 47% of women thought IAP present in their homes and the most common source was cooking. Symptoms like asthma, sweating, burns/rash, and headache had a significantly higher association in women using mud stove (P<0.05) than LPG stove. A strong association was found between cooking hours and health effects due to IAP (P< 0.004). Conclusions: IAP due to cooking and unfavorable housing conditions are associated with health problems in women. Knowledge regarding IAP is poor. Reasons for reliance on using mud stove needs to be addressed.